Legal Protection of Concurrent Creditor on Bankruptcy - Khairus Febryan; Dewi Sartika (Unram Law Review, 2018)
Bankruptcy is a method in the process of debt settlement in Indonesia through the Court, the regulation has amended several times and now the regulation of bankruptcy is regulated in The Act Number 37 Year 2004 of Bankruptcy and Postponement of Debt Repayment. In the Act, provides the debtor legal protection in the case by creditors of mass executions does concern, while the process to protect creditors from receivables refund from the debtor. The creditors are classified into 3 (three) criteria, i.e. : Separatist, Preferen and Concurrent, in this paper discussed about the legal protection to the concurrent creditor which must be clarified in the Act because of its position as a creditor who has no mortgage on his receivables.\ Legal protection, Bankruptcy, Creditors